PENGARUH MODEL PEMBELAJARAN BRAINSTORMING TERHADAP SIKAP PERCAYA DIRI SISWA PADA PELAJARAN PPKn - Kartoni, Novyanti; Alinurdin, Alinurdin (Instruksional, 2021)
Learning of brainstorming is the perfect one for the active students who has lack of self esteem in expression of asking and giving some opinions. The Brainstorming Learning could be motivate the students to give some ideas without interruption. To achieve the aims  of studying Brainstorming model is to find out if there are a positive and significant correlation between Brainstroming Learning and self esteem of the students on the subject of Civic Education in 8 grade Islamic Junior High School Nurul Hidayah Bojongsari City of Depok Academic Year 2018/2019.The Research Instrument of collecting data are validation questionnaire and Respons of students, also use analysis technique of quantitative such as Normality test, Realibity test, Correlation test and Regresion test. Acknowlegde that Brainstorming learning influences the self esteem of the students amount 86%. It means the Brainstorming Learning can change of self esteem from the students in Civic Education.